Legal Validity of Credit Agreement Deeds Not Made Before a Notary - Isvandrya, Silvira Rossa (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
Legislation requires the making of authentic deeds to be carried out in realizing the achievement of welfare, as well as legal protection for the Community according to their needs. Therefore, bank officials must ensure that all legal aspects related to the credit agreement have been completed and have provided adequate protection for the bank. Credit agreements at banks can be made by making private deeds and also with authentic deeds made by a notary. Credit agreements using notarial deeds are usually carried out after the procedures and methods for implementing a credit feasibility survey to the debtor have been approved by the bank. Therefore, the making of authentic notarial deeds in the case of bank credit agreements is read by a notary to the parties, with the aim that the parties making the agreement gain a clear understanding of the matters contained or the material of the credit agreement. The role of a notary in the preparation of credit agreement deeds carried out by the banking party is as an official authorized to prepare credit agreement deeds. Furthermore, the notary also plays a role in checking the guarantee of the object to which the mortgage is attached in terms of guaranteeing the legality of the object in order to avoid risks and anything that could possibly cause legal problems with the guaranteed object so that no party feels disadvantaged.